Competitive Factors of Fashion Retail Sector with Special Focus on SMEs - Gyorgy Gonda; Eva Gorgenyi-Hegyes; Robert Jeyakumar Nathan; Maria Fekete-Farkas (Economies, 2020)
Nowadays small and medium sized enterprises have become increasingly important in contribution to job creation and economic growth both in national and European level. Considering the rapidly and continuously changing business environment, due to the impacts of globalization and concentration, staying competitive is a great challenge for companies in the 21st century, especially in fashion retail sector. The current paper is intended to map the current situation of the sector—focusing primarily on SMEs—through the extensive literature review; and provide a better understanding of sector-specific competitive factors in fashion industry. The research methods are the analysis of different related articles, reports and other scientific literature sources, in-depth interviews and questionnaire survey. The survey was validated by confirmatory factor analysis, data were analyzed and evaluated through PLS-SEM model. The main findings of the study show that the most important competitive factor is the compliance with consumer needs. Furthermore, the research also points out that SME sector lag behind chains, thus, they need to focus more on better understanding and meeting consumer expectations. In this activity, it would be useful if they received EU and domestic support for educational assistance.